Not just nickel-and-dime: An analysis of journal articles winning Ig Nobel prize during 2011–2020 - Yeung, Andy Wai Kan (Malaysian Journal of Library and Information Science, 2022)
Ig Nobel prize is a satirical award given to achievements that are unusual, imaginative, and frequently produced in the form of journal articles. It was largely unknown how these award-winning articles were disseminated in the community in terms of academic citations and social media attentions. This study evaluated all journal articles winning the award during the period of 2011–2020 for their citation and social media performance metrics. There were 89 Ig Nobel prize-winning journal articles indexed by Scopus. On average, they were cited 42.5 ± 102.4 times, published in journals with mean impact factor of 3.476 ± 4.102, and mentioned 947.3 ± 2887.2 times and 263.2 ± 502.7 times on Facebook and Twitter, respectively. Over half of them were published in the first quartile journals and awarded within 2 years since publication. Though Ig Nobel prize was originally intended to be satirical, prize-winning articles themselves were indeed impactful in the academia.